A numerical algorithm for obtaining an optimal temperature distribution in a 3D triple layered cylindrical skin structure - Zhang, Le; Dai, Weizhong; Nassar, Raja (Computer Assisted Methods in Engineering and Science, 2007)
In recent years, there has been interest in research related to hyperthermia combined with radiation and cytotoxic drugs to enhance the killing of tumors. The objective is to control laser heating of the tumor so that the temperature of the normal tissue surrounding the tumor remains low enough so as.. not to cause damage to the tissue. To achieve this objective, it is important to obtain an optimal temperature field of the entire treatment region. In this paper, we develop a numerical algorithm for obtaining an optimal temperature distribution in a 3D triple layered cylindrical skin structure by pre-specifying the temperatures to be obtained at the center and perimeter of the treated region on the skin surface. The method is comprised of designing a laser irradiation pattern, solving a 3D Pennes' bioheat equation by a numerical scheme, and optimizing the laser power.